Zeatin Elicits Premature Erythrocyte Senescence Through Calcium and Oxidative Stress Mediated by the NOS/PKC/CK1α Signaling Axis - Iman A. Alajeyan; Jawaher Alsughayyir; Mohammad A. Alfhili (Dose-Response)
Objectives: Cytokinins are plant hormones that regulate cell growth and differentiation. In particular, zeatin (ZTN) delays cellular senescence of human fibroblasts and keratinocytes and exhibits anticancer activity. Chemotherapy-induced anemia is a major side effect of anticancer therapy secondary to premature senescence of red blood cells (RBCs). Herein, we investigated the biochemical and molecular mechanisms underlying ZTN action in human RBCs. Methods: Colorimetric assays were used to quantify hemolysis and related markers and flow cytometric analysis was applied to examine eryptosis through phosphatidylserine (PS) exposure by annexin-V-FITC, intracellular Ca 2+ by Fluo4/AM, reactive oxygen species (ROS) by H 2 DCFDA, and cell size from forward scatter (FSC). Results: ZTN at 200 μM induced significant hemolysis and K + , Na + , AST, and LDH leakage. ZTN also caused a significant increase in annexin-V-positive cells along with increased Fluo4 and DCF fluorescence and reduced FSC. Importantly, L-NAME, staurosporin, D4476, urea, sucrose, and polyethylene glycol 8000 (PEG) significantly ameliorated ZTN cytotoxicity. Conclusion: ZTN stimulates PS exposure, intracellular Ca 2+ elevation, oxidative stress, and cell shrinkage. The hemolytic potential of ZTN, mediated through nitric oxide synthase/protein kinase C/casein kinase 1α signaling axis, is sensitive to isosmotic urea, sucrose, and PEG availability. Altogether, the anticancer potential of ZTN must be reconsidered with prudence.